Isolation, purification and mode of action of antimicrobial peptides produced by lactic acid bacteria of dairy origin / Goh Hweh Fen - Goh , Hweh Fen (2016)
Lactic acid bacteria (LAB) are found in fermented food products. They help in improving shelf-life and enhance the flavour of food. They also produce bacteriocins to prevent the growth of undesirable bacteria. The goal of this study was to search for microbial strains with potent antimicrobial activity that can combat emerging food-borne pathogens and spoilage bacteria. In this study, LAB namely Lactococcus lactis A1, Weissella confusa A3 and Enterococcus faecium C1 were isolated from fermented cow milk and found to produce antimicrobial compounds. PCR amplification of genes encoding known bacteriocins proved that L. lactis A1 harboured Nis Z gene. As nisin has been well documented, it was not chosen for further investigations. E. faecium C1 did not harbour genes for enterocin A, B and P production. Therefore further tests were done to identify and characterise the bacteriocin from E. faecium C1. No gene encoding bacteriocin production was available for W. confusa. Both bacteriocins were purified through four steps namely ammonium sulphate precipitation, hydrophobic interaction, centrifugal filter, size separation concentrator and finally reverse phase HPLC. Both bacteriocins were active towards Bacillus cereus, Escherichia coli, Pseudomonas aeruginosa and Micrococcus luteus. The purified bacteriocins were named BacA3 and BacC1 for bacteriocin purified from Weissella confusa A3 and Enterococcus faecium C1 respectively. SDS-PAGE showed that the molecular weight of BacA3 was around 2.5 kDa. MALDI-TOF analysis suggested that BacA3 might be approximately 2.7 kDa. The molecular weight of BacC1 estimated by SDS-PAGE was around 10 kDa. The trypsin digested BacC1 showed unique molecular weight which did not match with any known proteins from UniProt database. BacA3 exhibited thermostability when exposed to temperature of 100 °C but BacC1 showed reduced activity after heating to 80 °C. Both BacA3 and BacC1 retained their activity at pH ranging from 2 to 6. When treated with proteinase and peptidase, both bacteriocins showed reduction in activity. Hence, confirmed the antimicrobial substances were of proteinaceous nature. The membrane permeability test using SYTOX® green nucleic acid stain showed that both bacteriocins caused significant disruptions to the test bacterial membrane and this was confirmed by transmission electron microscopy. The N-terminal sequence of BacA3 was VAPGEIVESL and BacC1 was GPXGPXGP. The search for genes related to virulence, superantigens and diseases by Rapid Annotation using Subsystem Technology (RAST) showed that both strains did not harbour the genes. The antibiotic resistance genes as listed in the pathogenicity island database were also absent in E. faecium C1. The virulence genes detected from the virulence factor database showed that 6 genes (Asm, SagA, EfaAfm, CdsA, UppS, BopD) present in C1 were also present in probiotic strain T110. The genomes of A3 and C1 showed the presence of several probiotic function genes. In vitro testing of viable W. confusa A3 and E. faecium C1 and their bacteriocins on milk also showed significant reduction of total bacterial count. Strains A3 and C1 were non-haemolytic and not antibiotic resistant. They therefore have high potential for application in the food industry as antimicrobial agents to extend the shelf-life of food products.